Frontispiece: An Incomplete Spin Transition Associated with a Z′=1→Z′=24 Crystallographic Symmetry Breaking. Issue 20 (10th April 2018) - Capel Berdiell, Izar; Kulmaczewski, Rafal; Cespedes, Oscar; Halcrow, Malcolm A.
Abstract : The cover image shows the twenty‐four crystallographically unique cations in the low‐temperature phase, of a spin‐crossover complex from the [Fe(bpp)2 ] 2+ family (bpp=2, 6‐dipyrazol‐1‐ylpyridine). Different molecules are high‐spin (silver), low‐spin (brown), or have a mixed spin‐state population (yellow) at 130 K, giving an approximate 1:1 high:low‐spin ratio overall. This is the most severe symmetry breaking yet reported in a spin‐crossover compound, and the number of independent molecules (Z'=24) is one of the highest known in a molecular crystal. More information can be found in the Communication by M. A. Halcrow et al. onpage 5055 ff.